Structural and functional condition of the left ventricle and the arterial wall stiffness in patients with essential hypertension - G. V. Dzyak; E. L. Kolesnik (Zaporožskij Medicinskij Žurnal)
Impact of the left ventricular hypertrophy (LVH) and increasing of the pulse wave velocity in aorta (PWV) at cardiovascular risk proved in various groups of patients.